SAT0687 Silicone breast implants and the risk of autoimmune diseases: real world analysis. (12th June 2018) - Watad, A.; Rosenberg, V.; Tiosano, S.; Cohen Tervaert, J.W.; Yavne, Y.; Shoenfeld, Y.; Shalev, V.; Chodick, G.; Amital, H.
Abstract : Background: Previous reports have suggested an association between silicone breast implants (SBIs) and connective tissue disorders. However, several epidemiological studies have produced inconsistent results. Objectives: To evaluate the association between SBIs and the most clinically relevant auto-immune diseases (ADs) using a large, population based database. Methods: In this cross-sectional study, we used the computerised databases of Maccabi Healthcare Services (MHS) which include up to 20 years of data on 2 million members. Women with SBIs were identified by procedure and diagnosis codes, clinical breast examinations and mammography referrals. ADs were identified using the International Classification of Diseases 9th revision (ICD-9) codes. SBIs-free women were matched by age group and socio-economic status (SES) in a ratio of 1:4. Multivariable logistic regression and Cox's proportional hazards models were performed. Results: We included 24, 651 SBI recipients and 98 604 matched SBIs free women in our study. The association between SBIs and AD was significant (p < 0.05) (adjusted OR 1.21, 95% CI 1.17–1.26). The strongest association with SBIs (OR >1.5, p<0.001) was recorded for systemic sclerosis (SSc) and sarcoidosis (OR of 1.99 and 1.67, respectively). Similar results were calculated when analysis was limited to cancer free women. Multivariable Cox regression model yielded a HR of 1.45 (95% CI 1.21–1.73) for being diagnosed with at least one AD in women with SBI compared to those without. Conclusions: SBIs seems to be associated with higher likelihood of auto-immune disease diagnosis. Acknowledgements: None Disclosure of Interest: None declared